Air quality during and after the Commonwealth Games 2018 in Australia: Multiple benefits of monitoring. (February 2021) - Kuhn, Tara; Jayaratne, Rohan; Thai, Phong K.; Christensen, Bryce; Liu, Xiaoting; Dunbabin, Matthew; Lamont, Riki; Zing, Isak; Wainwright, David; Witte, Christian; Neale, Donald; Morawska, Lidia
Abstract: Concerns about air quality were expressed in preparations for the Commonwealth Games (Games), which were held at the Gold Coast, Australia, from 4th to 15th April, 2018, an international sporting event attended by more than 6600 athletes and over 670, 000 visitors. Our aim was to trial application of low-cost sensors by conducting high spatial resolution air quality monitoring. An additional aim was to determine any impacts of the Games, and to involve in the process the relevant stakeholders. A network of 9 KOALA monitors measuring PM2.5 and carbon monoxide (CO), supported by one set of reference instruments and a meteorological station, were deployed for a 6 week period across a suburb hosting most of the Games activities. Due to community interest, a scaled down version of 3 monitors and a reference instrument operates to this date. We showed that the concentrations of both PM2.5 and CO were low during the Games (4 μg/m 3 and 0.112 ppm respectively), and that the Games did not result in deterioration of air quality. We demonstrated that the involvement of the stakeholders including the local authorities, the community and a high school resulted in an increased awareness of the importance of air quality monitoring, and elevated interest of the students in science of the environment. There was a high correlation between daily averages of PM2.5 measured by the monitors and the reference instrument (R 2  = 0.89) over a 12 month period, which supports low cost monitors as a viable option for long term air quality monitoring. Graphical abstract: Image 1 Highlights: Versatile new device employed for real-time PM2.5 and CO monitoring Low-cost air quality monitoring network at 2018 Commonwealth Games High correlation with reference instrumentation Successfully determined temporal and spatial variability of air quality